Targeting immunometabolism mediated by the IDO1 Pathway: A new mechanism of immune resistance in endometrial cancer - Passarelli, Anna; Pisano, Carmela; Cecere, Sabrina Chiara; Di Napoli, Marilena; Rossetti, Sabrina; Tambaro, Rosa; Ventriglia, Jole; Gherardi, Federica; Iannacone, Eva; Venanzio, Sergio Setola; Fiore, Francesco; Bartoletti, Michele; et al. (Frontiers in Immunology, 2022)
Immunotherapy is acquiring a primary role in treating endometrial cancer (EC) with a relevant benefit for many patients. Regardless, patients progressing during immunotherapy or those who are resistant represent an unmet need. The mechanisms of immune resistance and escape need to be better investigated. Here, we review the major mechanisms of immune escape activated by the indolamine 2,3-dioxygenase-1 (IDO1) pathway in EC and focus on potential therapeutic strategies based on IDO1 signaling pathway control. IDO1 catalyzes the first rate-limiting step of the so-called “kynurenine (Kyn) pathway,” which converts the essential amino acid L-tryptophan into the immunosuppressive metabolite L-kynurenine. Functionally, IDO1 has played a pivotal role in cancer immune escape by catalyzing the initial step of the Kyn pathway. The overexpression of IDO1 is also associated with poor prognosis in EC. These findings could lead to advantages in immunotherapy-based approaches as a rationale for overcoming the immune escape. Indeed, besides immune checkpoints, other mechanisms, including the IDO enzymes, contribute to the EC progression due to the immunosuppression induced by the tumor milieu. On the other hand, the IDO1 enzyme has recently emerged as both a promising therapeutic target and an unfavorable prognostic biomarker. This evidence provides the basis for translational strategies of immune combination, while IDO1 expression would serve as a potential prognostic biomarker in metastatic EC.